Gender diversity, institutional factors, and CEO compensation in China. Issue 1 (2nd January 2019) - Adithipyangkul, Pattarin; Leung, T. Y.
Abstract: Executive compensation has attracted public criticism and regulatory attention in various countries around the world. While previous research shows that a more powerful CEO receives greater compensation, less is known about how governance mechanisms and institutional forces mitigate or exacerbate CEO's abuse of power to inflate CEO pay. This article examines the impacts of gender diversity in compensation committees, government regulation, and subnational culture (Confucianism and socialist ideology) on CEO compensation in China. The analyses show that while government regulation, Confucianism, and socialist ideology can reduce CEO compensation, the effectiveness of each mechanism appears to be context-specific. Different institutional forces can deter CEO power from different sources. Institutional environment can augment or limit CEO's abuse of power to extract greater compensation from the company. We do not find gender diversity in compensation committees to be effective in restraining CEO compensation. Our results are robust to different measures of pay excessiveness (absolute and relative terms) and after controlling for endogeneity. This research suggests that practitioners should consider both CEO characteristics and institutional environment when they design a corporate governance system.